Airlines and developing countries - Button, Kenneth (Advances in airline economics ;, 2023)
Given the potential size of some of the markets involved and the comparative advantages in serving them, it is surprising to see a relative sparsity of airline activity in developing countries. Lack of suitable data, limited interest, and the comparatively small scale of aviation markets in many of these countries provide some of the explanations for this relative neglect. Airlines and Developing Countries works to address some of the key challenges that are confronting airlines and public policy makers, helping to fill a number of voids in our knowledge. The approaches of the various expert contributors offer a range of technical, empirical, historical, and institutional analyses that consider long-term patterns of economic development and look at how airlines have influenced this going back as far as the 1930s.